Cosplay di Kalangan Muslim: Analisis Perilaku Meniru Karakter Anime dalam Perspektif Hadis Tasyabbuh - Najwa Hafana; Nasrulloh (Al-Kindi, 2026)
The rapid growth of cosplay culture among young Indonesian Muslims raises important theological questions regarding the hadith of tasyabbuh (imitation), which prohibits Muslims from resembling certain groups. This study analyzes cosplay behavior among Muslim youth through the lens of the tasyabbuh hadith (HR. Abu Dawud No. 4031) using a qualitative phenomenological approach. Data were collected via an online questionnaire distributed to four Muslim cosplayers with at least two years of active experience. Data analysis followed the Miles and Huberman interactive model. The findings reveal: (1) Muslim cosplayers are motivated by artistic expression, self-exploration, and social belonging; (2) informants construct diverse interpretations of tasyabbuh, including emphasis on intention, semantic reinterpretation of